Maternal and Infant Health Inequality: New Evidence from Linked Administrative Data - Kate Kennedy-Moulton; Sarah Miller; Petra Persson; Maya Rossin-Slater; Laura R. Wherry; Gloria Aldana (Institute of Labor Economics (IZA), 2022)
We use linked administrative data on the universe of California births to provide novel evidence on economic inequality in infant and maternal health. Infants and mothers at the top of the income distribution have worse birth and morbidity outcomes than their lowest-income counterparts, but are nevertheless the least likely to die in the year following birth. Racial disparities swamp these income disparities, with no racial convergence in health outcomes as income rises. A comparison with Sweden shows that infant and maternal health is worse in California at virtually all income levels.
Keywords: I14; 330; maternal and infant health; health disparities; administrative data